Formação profissional e mediação pedagógica na era digital: educar para os meios e os meios para educar - Cruz, José Anderson Santos [UNESP] (2015)
This research had set the growth of postgraduate courses in Didactics and methodology of higher education, techonological advances in a globalised society with educational transformations. hus, to address, discuss and show the necessity of the professor/teacher to understand the current technological advances, in order to integrate with contemporary digital technologies. In this sense it is essential and relevant to the use of information and communication technologies (ICT), particularly the use of television in the classroom, and that this professional can handle and use such technologies as a mediator in the teaching - learning process of form didactics (teaching method with links to certain stimuli and responses, instigating and adaptation to the knowledge generated by the information-the teacher as mediator, education and motivating learning with the ferrets caused by pedagogical means and mediations). For this, it is prudent to wonder how the specialization courses for teaching in higher education lead to insert and contact with the technologies in the formation of these teachers? And yet, when using the television, which possess knowledge about Digital Interactive Television (Dtv) or simply about Digital Television (TVD) and its possibilities? With applied approach in two ways-the teacher-mediator in the classroom, and the students-future or already a teacher preparing for a career in higher education. We used the methodology of exploratory descriptive character. In addition to bibliographic survey about the topic. And, also, interviews with teachers and students of group a private institution of higher education of the graduate course, level specialization in Didactics and methodology of higher education. It was observed in this scenario, the need for vocational training is tied in an awareness and education to use the means, so that teachers, specialized or professional future of higher education, may use the means of critically...